Front Cover: Electrochemical Activity of Cytochrome P450 1A2: The Relevance of O2 Control and the Natural Electron Donor (ChemElectroChem 3/2021). Issue 3 (14th January 2021) - Silveira, Célia M.; Rodrigues, Patrícia R.; Ghach, Wissam; Pereira, Sofia A.; Esteves, Francisco; Kranendonk, Michel; Etienne, Mathieu; Almeida, M. Gabriela
Abstract : The Front Cover shows the electrochemical response of the human monooxygenase enzyme, cytochrome P450 1A2 (CYP1A2), in the presence of its natural electron donor partner, cytochrome P450 oxidoreductase (CPR), highlighting the role of the interaction with the latter in the stabilization of CYP1A2 and attaining the electrochemically driven activity towards O2 . The picture also emphasizes the protein entrapment matrix, a biocompatible sol‐gel film, which proved to be crucial for the achievement of interfacial electron transfer. More information can be found in the Article by M. G. Almeida and co‐workers .